O desenvolvimento do sentido de realidade em Freud - Repa, Renata Felis Bazzo (2013)
The present study sought to examine the concept of sense of reality in the work of Sigmund Freud. Although widely used in psychoanalytic research, there are few definitions of the concept, leaving many questions about their assignments in the function of apprehending reality. Contributes to that the fact that Freud uses it only once, under that name in the text The malaise in civilization (1930), when he states that there is a development of the sense of reality. This Freudian thesis has become common in many subsequent researches in psychoanalysis which sought to establish the ways in which this development would occur. The present study aimed to investigate whether and how the sense of reality could develop. For this, we define the concept by investigating the notion of reality feeling. Subsequently, the study conducts a survey of the use of this concept in the psychoanalytic tradition, his constant connection with that development and the problems that this junction could bring to psychoanalytic treatment. In the next phase, we established what could be the psychic development for Freud. The last step consists, in its turn, an intersection of the hypotheses about the meaning of reality sense with the development modes found in Freud. This work suggests the following results: it is possible to find different conceptions of development for the sense of reality in Freud, but none of them suggests the existence of a development along the lines of epigenesis or as a totalizing process